The Role of Oxidative Stress in the Pathomechanism of Congenital Malformations. (30th December 2018) - Laforgia, Nicola; Di Mauro, Antonio; Favia Guarnieri, Giovanna; Varvara, Dora; De Cosmo, Lucrezia; Panza, Raffaella; Capozza, Manuela; Baldassarre, Maria Elisabetta; Resta, Nicoletta
Abstract : Congenital anomalies are significant causes of mortality and morbidity in infancy and childhood. Embryogenesis requires specific signaling pathways to regulate cell proliferation and differentiation. These signaling pathways are sensitive to endogenous and exogenous agents able to produce several structural changes of the developing fetus. Oxidative stress, due to an imbalance between the production of reactive oxygen species and antioxidant defenses, disrupts signaling pathways with a causative role in birth defects. This review provides a basis for understanding the role of oxidative stress in the pathomechanism of congenital malformations, discussing the mechanisms related to some congenital malformations. New insights in the knowledge of pathomechanism of oxidative stress-related congenital malformations, according to experimental and human studies, represent the basis of possible clinical applications in screening, prevention, and therapies.